Recommmendations for the diagnostic algorithm in lung cancer. Consensus statement of the Macedonian respiratory society and the Macedonian association of pathology - Zdraveska, Marija; Todevski Dejan; Rexhepi Arben; Tatabitovska Aleksandra; Ismaili, Irfan; Kostadinova Kunovska, Slavica; Bogdanovska Todorovska, Magdalena; Stefanovski Tome; Petrushevska, Gordana (Македонско лекарско друштво = Macedonian Medical Association, 2019)
Lung cancer is the “number one cancer killer” in the world. Its prevalence is associated to smoking as the primary cause, although air pollution in general and genetic factors are also in stake. The mortality especially from advanced stage lung cancer is still high, although there has been a significant improvement in the past 10 years, mostly due to the introduction of novel compounds such as targeted and immunological treatment. The advances in the treatment of NSCLC have imposed updating of the guidelines for the diagnostic procedure and screening of LC, for the indications for molecular testing as well as for targeted selection of patients who shall benefit the most of the novel treatment modalities. These recommendations shall fulfill their purpose only if implemented in the educational curriculum and if incorporated in the healthcare system strategies.
Keywords: Guidelines; non-small cell lung cancer; molecular diagnosis; diagnostic algorithm